MAKNA PERMUFAKATAN JAHAT DALAM PASAL 15 UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI, DIKAJI DARI HERMENEUTIKA HUKUM (STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 21/PUU-XIV/2016) - Tantri Kartika (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Evil agreement in corruption is regulated in Article 15 of Law Number 20 Year 2001 concerning Amendment to Law No. 31 of 1999 concerning Eradication of Corruption Crime. In Article 15 of Law Number 20 Year 2001 concerning the Eradication of Corruption Crime, people who are proven to have committed conspiracy to commit corruption can be subject to maximum imprisonment for life, or as short as four years in prison. A fine of Rp. 200 million to Rp. 1 billion will also be given to defendants for conspiracy. The conclusion is in interpreting Article 15 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes as amended by Law Number 20 of 2001 using Hans-Georg Gadamer's study of legal hermeneutics law, which according to him can use philosophical hermeneutics to take ontology assignments , that is, the task with regard to the inevitable relationship between the text and the reader, the past, the present that enables understanding. If speaking of the past it is interpreted historically interpretive (interpretation according to history), in this case the judge to obtain an explanation of a provision examining the talk of people regarding the provisions during the formation process (wetshistorisch), or the judge must examine the previous provisions that precedes the current provisions (rechtshistorisch). A judge must see history from the meaning of evil agreement.